Steels : microstructure and properties - Bhadeshia, H. K. D. H. (Harshad Kumar Dharamshi Hansraj), 1953- (Elsevier, Butterworth-Heinemann, 2006)
The most comprehensive and up-to-date textbook on the microstructure and properties of steels.
Previous edition: London : Edward Arnold, 1995. Primary author, Honeycombe.
Keywords: Steel.; Steel -- Metallurgy.; Steel -- Metallography.; Acier.; Acier -- Métallurgie.; Acier -- Métallographie.; stalk (plant material); stems (object components); steels (firearm components); helves.; honing steels.; TECHNOLOGY & ENGINEERING -- Metallurgy.; Steel; Steel -- Metallography; Steel -- Metallurgy; dissertations.; Academic theses; Academic theses.; Thèses et écrits académiques.